A STUDY ON THE PERFORMANCE OF SMALL SCALE SECTORS IN KANYAKUMARI DISTRICT - Sugin Raj; Raja, K.V.Soundara (International Journal of Research -GRANTHAALAYAH, 2016)
Micro, Small and Medium Enterprises (MSMEs) sector has emerged as a highly vibrant and dynamic sector of the Indian economy over the last five decades. MSMEs not only play a crucial role in providing large employment opportunities at comparatively lower capital cost than large industries but also help in industrialization of rural and backward areas. This paper assesses the growth and performance of MSMEs in Kanyakumari district on the number of enterprises, investment, employment generated and money value of the production. The performance of MSMEs assessed with the secondary data from 1984-85 to 2014-2015